The Correlation between Serum Estradiol Level and Body Mass Index in Postmenopausal Women: A cross-sectional study at the Menopause Clinic, Siriraj Hospital - Kitirat Techatraisak; Kittiyaporn Wattayanon (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives:To examine correlation between serum level of estradiol (E2) and body mass index (BMI) in postmenopausal women at a menopause clinic of a tertiary care university hospital.Materials and Methods:A retrospective cross-sectional study was performed at the Menopause Clinic, Faculty of Medicine Siriraj Hospital, Mahidol University. One hundred and twenty five consecutive medical records of menopausal women attending the menopause clinic, including both natural and surgical menopause were reviewed. All of them never received hormonal treatment or did not receive any hormonal treatment at least one year at the time of this study. All were confirmed to have serum FSH level ≥ 40 IU/L. Baseline characteristic, data on serum level of E2, BMI, type of menopause and duration of menopause were extracted. Correlation between serum level of E2 and BMI was evaluated by the Statistics Package for the Social Sciences Program (SPSS 18.0 statistical package). Pearson correlation analysis was used to demonstrate the correlation between serum E2 level and BMI, with a p value less than 0.05 considered as statistically significant.results: Of all 125 patients, the majority were natural menopausal cases (81.6%). Mean E2 level and BMI were 20.38±16.61 pg/ml and 22.96±3.65 kg/m2 respectively. No significant correlation between serum E2 level and BMI was demonstrated (r = - 0.101, p = 0.265). Also no correlation was observed in different type of menopause, different duration of menopause and different BMI classification.Conclusion: There was no significant correlation between serum level of E2 and BMI in postmenopausal women of this study population.